2013
DOI: 10.1002/anie.201304451
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Nitrene Transfer to Sulfides Catalyzed by a Chiral Iron Complex

Abstract: Sulfimides are nitrogen analogues of sulfoxides. [1] In organic synthesis, they serve as useful intermediates [1,2] and have been applied as efficient ligands for metal catalysts. [3] Because of their unique biological properties, [1a, 4] sulfimides have also gained considerable attention in agricultural science and medicinal chemistry. As sulfoxides, sulfimides are chiral and have a stereogenic center at the sulfur atom if they originate from unsymmetrically substituted sulfides. Although sulfimides can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(62 citation statements)
references
References 69 publications
0
62
0
Order By: Relevance
“…Indeed, the specific activities of the enzyme catalysts reported here compare favorably with enantioselective iron-based catalysts, which routinely require catalyst loadings of 10 mol %. 9b Furthermore, engineering the holoenzyme or reductase domain to favor one-electron transfers might improve the proportion of desired product relative to azide reduction, which could allow reaction with more challenging organic acceptor substrates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the specific activities of the enzyme catalysts reported here compare favorably with enantioselective iron-based catalysts, which routinely require catalyst loadings of 10 mol %. 9b Furthermore, engineering the holoenzyme or reductase domain to favor one-electron transfers might improve the proportion of desired product relative to azide reduction, which could allow reaction with more challenging organic acceptor substrates.…”
Section: Resultsmentioning
confidence: 99%
“…8 Subsequent oxidation to form sulfoximines can be achieved with good chirality transfer, 9 and the resulting compounds are a promising source of novel derivatives of therapeutic small molecules. 10 Furthermore, sulfides substituted at the sulfur position with allyl groups can undergo a 2,3-sigmatropic rearrangement upon sulfimidation, resulting in formation of a new C–N bond.…”
mentioning
confidence: 99%
“…Recently, a considerable improvement in the enantioselective synthesis of sulfimides and sulfoximines has been achieved by using a catalyst consisting of an iron(III) salt combined with a PyBOX ligand. 53,54 The investigation of enantioselective sulfimidations showed that 5-10 mol% of Fe(dmhdCl) 3 (dmhd = 4-chloro-2,6-dimethyl-3,5-heptanedionate) along with 5-10 mol% of (R,R)-Ph-PyBOX 82 and PhIQNTs as nitrene source was the View Article Online best combination providing sulfimides 83 in high yields and enantiomeric ratios of up to 96 : 4 for a broad substrate scope (Scheme 30, top). Noteworthy, the reactions proceeded smoothly in acetone (cheap, low toxicity) at low temperature, without exclusion of air and moisture.…”
Section: Scheme 24mentioning
confidence: 99%
“…2,6-bis(oxazolin-2-yl)pyridines are versatile ligands assisted in metal catalysts for various organic transformation due to their feasible syntheses and easy modification of the steric and electronic properties, in particular, adjusting enantioselectivity via introducing chiral center into appropriate place of ligand has led to tremendous efficient chiral catalysts for organic building [49][50][51][52]. Description of their catalysis behavior for polymerization, however, is conspiculously less, and reported examples are only limited in chromium [53], iron [54] and ruthenium catalysts [55].…”
Section: The Tunability Of the Selectivitymentioning
confidence: 99%